A multimodal nano agent for image-guided cancer surgery. (October 2015) - Zheng, Jinzi; Muhanna, Nidal; De Souza, Raquel; Wada, Hironobu; Chan, Harley; Akens, Margarete K.; Anayama, Takashi; Yasufuku, Kazuhiro; Serra, Stefano; Irish, Jonathan; Allen, Christine; Jaffray, David
Abstract: Intraoperative imaging technologies including computed tomography and fluorescence optical imaging are becoming routine tools in the cancer surgery operating room. They constitute an enabling platform for high performance surgical resections that assure local control while minimizing morbidity. New contrast agents that can increase the sensitivity and visualization power of existing intraoperative imaging techniques will further enhance their clinical benefit. We report here the development, detection and visualization of a dual-modality computed tomography and near-infrared fluorescence nano liposomal agent (CF800) in multiple preclinical animal models of cancer. We describe the successful application of this agent for combined preoperative computed tomography based three-dimensional surgical planning and intraoperative target mapping (>200 Hounsfield Units enhancement), as well as near-infrared fluorescence guided resection (>5-fold tumor-to-background ratio). These results strongly support the clinical advancement of this agent for image-guided surgery with potential to improve lesion localization, margin delineation and metastatic lymph node detection.